Information professionals in 2010 - Tejada-Artigas, Carlos-Miguel (Anuario ThinkEPI, 2011)
Some key reports that have appeared in 2010 related to professional development are commented. Topics include public libraries, university libraries, new profiles and labour market in the information and documentation area.